226 Management of Liver Trauma: Outcomes at One of Europe's Most Active HPB and Liver Transplant Centres. (4th May 2021) - Edwards, M; Laing, R
Abstract: Introduction: The management of liver trauma (LT) has gradually moved away from surgery and more towards conservative or interventional radiological management. Positive outcomes depend upon careful selection for non-operative management, and to avoid surgical intervention in all grade I-III injuries unless haemodynamically unstable following resuscitation. This study investigated the management of all LT patients over a 12-month period at our institution. Method: We undertook a retrospective study of all patients admitted with LT in 2019 (n = 60). We assessed records to determine the grade of LT (I-VI), concurrent injuries, their management, length of stay and outcomes. Results: Of the 60 patients admitted with LT, 43 were male (72%) and 41 patients (68%) sustained injuries to multiple organs. 53/60 patients (88%) sustained injuries classified as grade 3 or below. In patients with multiple organ injuries, 7/41 (17%) underwent intervention compared to 7/12 (58%) in those with isolated LT. No deaths were recorded in patients with LT, and 6 people died in the multiple injury group (mortality 10%). Any form of intervention was associated with a doubling in average length of stay. Conclusions: Non-operative management underpins most isolated LT care; if this fails or is associated with multiple organ traumas, morbidity and mortality rise dramatically.